Money Talks. Personal reflections from a systemic therapist on inequality, speaking out, and leaving the NHS - Oates, Julie (Murmurations: Journal of Transformative Systemic Practice, 2022)
Recognising the historical development of systemic theory and practice from its radical roots, I reflect on my positioning as a systemic therapist within the National Health Service (NHS) in the UK in 2020, and describe my journey from family therapist into community based systemic activism which seeks to directly address structural inequality. The concept and practice of Poverty Truth Commissions are examined through a systemic lens, and I outline the design influences in its set up locally, mapping those against historic and current systemic thinking. In the process, I examine my own relationship to money, status, voicing and work.